2021
DOI: 10.1177/15266028211025046
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Results of Carotid Artery Stenting Using Low-Profile Dual-Metal Layer Nitinol Micromesh Stents in Relation to Single-Layer Carotid Stents

Abstract: Purpose: To evaluate patients characteristics, procedural details, perioperative outcomes, and midterm results of carotid artery stenting (CAS) performed with the Roadsaver/Casper stent (Terumo Corp, Tokyo, Japan) as compared to concurrent patients treated with other commercially available carotid stents. Materials and Methods: This is a single-center, retrospective, nonrandomized study including 200 consecutive patients who underwent a total of 205 elective CAS procedures due to severe internal carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…15 A comparison study conducted by Kahlberg et al reported almost similar results in both the groups in terms of postprocedural adverse events, namely, TIA/stroke/mortality with 3% in dual-layer stenting group and 1% in single-layer stenting group. 16 This result is in same line with our study results of similar percentage population in both the groups presented postprocedural adverse events (26.32% in single-layer stenting group and 27.27% in dual-layer stenting group presented TIA). Lal et al found several stents used, lesion characteristics (length, ulceration), and procedural related risk factors of CAS playing a major role in CAS outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…15 A comparison study conducted by Kahlberg et al reported almost similar results in both the groups in terms of postprocedural adverse events, namely, TIA/stroke/mortality with 3% in dual-layer stenting group and 1% in single-layer stenting group. 16 This result is in same line with our study results of similar percentage population in both the groups presented postprocedural adverse events (26.32% in single-layer stenting group and 27.27% in dual-layer stenting group presented TIA). Lal et al found several stents used, lesion characteristics (length, ulceration), and procedural related risk factors of CAS playing a major role in CAS outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…However, available data remain very limited and only small studies have been published, indicating optimistic results [ 55 57 ]. Short- and long-term safety and efficacy of a dual-layer micromesh stent (DLMS) has already been shown in a number of studies [ 21 , 58 , 59 ]. A current multi-national, multi-specialty study aims to expand the clinical evidence base and confirm the good performance of the DLMS, now in a large, unselected patient cohort eligible for an elective CAS treatment as per routine care.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 reports the literature search and the process of papers selection for this study. After the screening process and duplicate studies removal, a total of 14 papers [16][17][18][19][20][21][22][23][24][25][26][27][28][29] were included in the analysis. Tables 1 and 2 report the characteristics of the studies included.…”
Section: Study Selection Characteristics and Quality Assessmentmentioning
confidence: 99%